Metaphor and the Natural Semantic Metalanguage - Wearing, Catherine (Journal of pragmatics, 2009)
This paper examines the account of metaphor developed within the Natural Semantic Metalanguage (NSM) framework. It is claimed by this view that metaphorical content is paraphraseable, and that the use of metaphor can be described via a cultural script. I explore the importance of paraphrasing metaphors for the NSM approach, and argue that the prospects for successful paraphrases are less promising than has been claimed. I then show that the cultural script does not suffice to explain how metaphors work, and describe how the script must be supplemented to generate a more adequate explanation.